Comparison of Fundus Fluorescein Angiography, Optical Coherence Tomography, and Optical Coherence Tomography Angiography Features of Macular Changes in Eales Disease: A Case Series - Naveed, Sana; Afzal, Tahira; Anjum, Summaya; Rehman, Uzma; Sohail, Salman; Amjad, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Eales disease is an idiopathic inflammatory retinal vasculopathy that predominantly affects young adults and is associated with significant visual morbidity. Objective: To compare FFA, OCT, and OCTA features of macular changes in patients with Eales disease and to assess the relative contribution of each modality in detecting vision-threatening macular pathology. Methods: This descriptive, cross-sectional study was conducted at Alshifa Eye Trust Hospital, Rawalpindi, from September 2024 to February 2025. A total of 42 patients diagnosed with Eales disease were enrolled using non-probability consecutive sampling. All patients underwent comprehensive ophthalmic examination and macular evaluation using FFA, OCT, and OCTA. Macular leakage, ischemia, and capillary non-perfusion were assessed on FFA; structural macular abnormalities were evaluated on OCT; and microvascular alterations, including foveal avascular zone (FAZ) changes and capillary plexus dropout, were analyzed on OCTA. Results: The mean age of patients was 31.8 ± 7.4 years, with a marked male predominance (81.0%). Macular leakage was detected on FFA in 58.6% of eyes, while macular ischemia was present in 36.2%. OCT demonstrated cystoid macular edema in 44.8% of eyes with a mean central subfield thickness of 382 ± 64 µm. OCTA revealed FAZ abnormalities in 74.1% of eyes, with deep capillary plexus dropout observed in 56.9% of eyes. Conclusion: Macular involvement is common in Eales disease and is best characterized using a multimodal imaging approach. While FFA and OCT remain essential for evaluating vascular leakage and structural changes, OCTA provides superior detection of macular ischemia and microvascular compromise, which are strongly associated with visual impairment.